Basic Electricity and Electronics Subjects using Canva as a Learning Medium - Avraam Ledentsov; Septy Fatmawati; Putri Seviawani (International Institute for Advanced Science & Technology (IIAST), 2023)
In today's ever-evolving educational landscape, the integration of innovative teaching methods and tools is essential to engage and educate students effectively. This research delves into the feasibility of employing Canva as a learning medium in Basic Electricity and Electronics courses, aiming to enhance the learning experience in these critical subjects. The study employed a structured questionnaire as its primary research instrument, targeting a diverse group of participants, including subject matter experts, educators, and students. The research focused on evaluating Canva's validity, reliability, and practicality within the context of pedagogy. The validation process, conducted by experts and educators, yielded an average validation score of 0.83, comfortably exceeding the established validity threshold (≥ 0.667). This substantiates Canva's categorization as a valid instructional medium for Basic Electricity and Electronics. The assessment of media reliability, measured using Cronbach's Alpha, produced a commendable score of 0.731, demonstrating high reliability. This underscores Canva's consistency as a valuable learning resource. Furthermore, practicality assessments by both teachers and students resulted in average scores of 90% and 86%, respectively. These scores affirm Canva's high practicality, making it a well-received and user-friendly tool in both teaching and learning contexts. In conclusion, this comprehensive evaluation highlights Canva as a suitable and effective addition to the Basic Electricity and Electronics curriculum. Its successful implementation represents a novel approach to enhancing engagement and comprehension among students in these subjects. The research contributes to the broader discourse on innovative pedagogical strategies and their potential to transform science and technology education. The findings support the notion that Canva serves as a valuable tool for educators seeking to create a dynamic and interactive learning environment in the realm of Basic Electricity and Electronics.